Ecogeomorphology of coastal deltaic floodplains and estuaries in an active delta: Insights from the Atchafalaya Coastal Basin. (31st October 2019) - Twilley, R.R.; Day, J.W.; Bevington, A.E.; Castañeda-Moya, E.; Christensen, A.; Holm, G.; Heffner, L.R.; Lane, R.; McCall, A.; Aarons, A.; Li, S.; Freeman, A.; et al.
Abstract: We present here an integrated analysis of coastal deltaic floodplains in the active Atchafalaya Coastal Basin coupled to downstream deltaic estuaries to review how ecosystem properties self-organize around fluvial processes during river re-occupation as part of the delta cycle. The flood pulse of the river is critical to providing autogenic feedbacks between flow patterns, sediment delivery, vegetation productivity, and organic/inorganic accretion that produce spatial patterns of land elevation, habitat diversity, and estuary dynamics. Coastal deltaic floodplains form in the proximal region of an active delta as bar-shaped islands with interdistributary bays shape hydrogeomorphic zones influenced by both geophysical and ecological processes. Hydrogeomorphic zones in coastal deltaic floodplains of the proximal sedimentation zone can also be defined by time since subaerial emergence accounts for variability in vegetation community composition and soil successional development. The reduction in sedimentation and increase in both above- and belowground biomass associated with formation of hydrogeomorphic zones results in significant increase in organic matter density in soils, with higher N:P ratios reflecting the biotic feedback of ecological succession on delta floodplain development. In both the proximal and distal sedimentation regions, episodic events, such as river floods and cold fronts, control seasonal water levels, marsh platform inundation, and increase in elevation capital. In coastal deltaic floodplains, an increase in vegetation height and density has a twofold effect: it favors trapping of sediment on the islands; whereas an increase in roughness deflects water flow and sediment into the channels thus bypassing the marsh surface. There is evidence that this is in contrast to more constant positive feedback of vegetation on sedimentation in distal estuarine marsh platforms. Delta estuaries go through a transformation from a near-riverine estuary in the winter-spring season to a near-marine lagoon in the summer-fall season. Geomorphological displacement of vegetation types occurs as platform elevation increases in the proximal sedimentation zone as delta landform emerges, with specific vegetation dominating the respective subtidal, intertidal and supratidal hydrogeomorphic zones. This does not occur in the distal sedimentation zone that lack sediment input as marsh platform elevation decreases. This is due to presence of salinity and H2 S that limit the capacity of biotic feedbacks to contribute to marsh stability. The growth of a coastal deltaic floodplain in the proximal sedimentation region of Atchafalaya Coastal Basin along with stable estuarine marshes in distal sedimentation region demonstrate the value of long-term riverine influence by preventing loss of wetland platform elevation.